Assessing Knowledge and Perceptions of Health Care Workers toward Novel Coronavirus (COVID-19) (Medico Legal Update, 2020)
Objective: To assess the knowledge and perceptions of health care workers towards coronavirus (COVID-19)in most of the governorates of Iraq.Method: A cross-sectional survey, web-based study was conducted among HCWs about COVID- 19 duringthe last two weeks of April 2020. Knowledge and Perception were assessed by five components adaptedfrom the Ebola knowledge scale, and A 7-item instrument this part was developed using WHO coursematerials on Emerging respiratory for viruses COVID-19 and distributed randomly to HCWs using socialmedia. Descriptive statistics were used to express participants’ demographic information, mean knowledgescore and mean Perception score of HCWs. Chi squares tests were used to assess the association betweenstudy variables and Perception questions was used to identify the level of association among variables at thesignificance level of p